Two new species of Smicridea (Rhyacophylax) Müller 1879 (Trichoptera: Hydropsychidae) from Atlantic Forest, Brazil - Santana, Vitória; Desiderio, Gleison Robson; Hamada, Neusa (Zootaxa, 2021)
Smicridea (Rhyacophylax) Müller 1879 contains 106 species, 41 of which occur in Brazil, mainly in the Atlantic Forest biome. Despite its diversity, it is estimated that many undescribed species are believed to be housed in scientific collections, waiting to be described. Smicridea specimens housed in two Brazilian insect collections (Coleção Entomológica Professor José Alfredo Pinheiro Dutra, Rio de Janeiro and Museu de Zoologia da Universidade de São Paulo, São Paulo) were examined and two new species of S. (Rhyacophylax) were detected. The objective of this study is to describe and illustrate these species. Smicridea (Rhyacophylax) boraceia sp. nov. and Smicridea (Rhyacophylax) dumasi sp. nov. inhabit the Atlantic forest biome and can be recognized mainly by the morphology of tergum X and the phallic apparatus. Six species groups are recognized in S. (Rhyacophylax); however, the two new species described here cannot be placed in any of these groups.